Memory and Learning Deficits Are Associated With Ca2+ Dyshomeostasis in Normal Aging - Uryash, Arkady; Flores, Valentina; Adams, Jose A.; Allen, Paul D.; Lopez, Jose R. (Frontiers in Aging Neuroscience, 2020)
ABSTRACT. Neuronal intracellular Ca2+ homeostasis is critical to the normal physiological functions of neurons and neuronal Ca2+ dyshomeostasis has been associated with age related decline of cognitive functions. Accumulated evidence indicates that the underlying mechanism for this is that abnormal intracellular Ca2+ levels stimulate dysregulation of intracellular signaling, which subsequently induces neuronal cell death. We examined intracellular Ca2+ homeostasis in cortical (in vivo) and hippocampal (in vitro) neurons from young (3-mos), middle-age (12-mos), and aged (24-mos) wild type C57BL6J mice. We found a progressive age-related elevation of intracellular resting calcium ([Ca2+]r) in cortical (in vivo) and hippocampal (in vitro) neurons associated with increased hippocampal neuronal calpain activity and reduced cell viability. In vitro, removal of extracellular Ca2+ or treatment with SAR7334 or dantrolene reduced [Ca2+]r in all age groups and dantrolene treatment lowered calpain activity and increased cell viability. In vivo, both middle-age and aged mice showed cognitive deficits compared to young mice, which improved after dantrolene treatment. These findings support the hypothesis that intracellular Ca2+ dyshomeostasis is a major mechanism underlying the cognitive deficits seen in both normal aging and degenerative neurologic diseases.